Limnology and Fisheries of the Kushiyara River, Bangladesh - Islam, M. M.; Akhi, S. A.; Faruque, M. H. (Journal of Scientific Research, 2019)
A study was conducted in November 2015 to assess the limnological and fisheries conditions of the Kushiyara river, Bangladesh. This study used laboratory techniques, face-to-face interviews and focus group discussions. This study collected water, phytoplankton, zooplankton and benthos from different sites of the river. It found that the water quality parameters such as dissolved oxygen, pH, temperature, turbidity, electrical conductivity, total dissolved solids and sodium chloride of the Kushiyara river are within the standard level for sustaining aquatic life. In the current study, six phytoplankton groups of 19 genera and three groups of zooplankton (4 genera of Rotifers, 3 genera of Copepods and 5 genera of Cladoceras) are recorded. This indicates good ecological conditions of the river water. The current study also recorded 9 groups of benthos, indicating a stable environmental condition in the river for benthos. Diverse kinds of fishing gear were found to operate in this study. They were used to catch almost similar species of fishes using almost similar catching mechanism. The peak and lean seasons for fishing as well as the number, types, length and weight of species of fishes are observed. Overall this study found good water quality and rich biodiversity in the Kushiyara river.